2-i/5+i = (2-i)*(5+i)ֿ¹
As (x+iy)ֿ¹ = (x+iy)*/||(x+iy)||²
(5+i)ֿ¹ = (5-i)/(5²+1²) = (5-i)/26
So (2-i)*(5+i)ֿ¹ = (2-i)(5-i)/26
= (10 -2i - 5i - 1)/26 = (9 -7i)/26 = 9/26 - (7/26)i
Another way to work it without having to know what the recipical is etc is this:
2-i/5+i = (x+iy) - as the answer can always be expressed an complex number
So
2 - i = (5+i)(x+iy) = 5x + 5yi + xi - y = 5x - y +(x+5y)i
Therefore this splits into two simultaneous equations:
5x - 1y = 2 ..............(1)
1x + 5y = -1 ............. (2)
Multiply (1) by 5 and add (1) and (2)
25x - 5y = 10 ..............(1)*5
1x + 5y = -1 ............. (2)
_________________________
26x + 0y = 9
So x = 9/26
Substitute this back into (1) to get y
5(9/26) - y = 2
y = 45/26 - 2 = (45-52)/26 = -7/26
So 2-i/5+i = 9/26 - (7/26)y
2007-01-09 03:35:24
·
answer #1
·
answered by Andy 2
·
0⤊
0⤋
You need to multiply the numerator and denominator by the complex conjugate of the denominator. In this case, the denominator is 5 + i, so the conjugate is 5 - i. That gives you [(2 - i)(5 - i)]/[(5 + i)(5 - i)] = (10 - 5i - 2i + i^2)/(25 + 5i - 5i - i^2) = (10 - 7i - 1)/(25 + 1) = (9 - 7i)/26 = 9/26 - (7/26)i. This works because multiplying the denominator by its complex conjugate always gives a real number as the denominator.
2007-01-09 03:12:33
·
answer #2
·
answered by DavidK93 7
·
0⤊
0⤋
2-i/5+i =
2 + (4/5)i
a=2
b=4/5
or did you mean (2-i)/(5+i)?
then multiply numerator and denominator by
(5-i) which in the denominator's complex conjugate. We have
[(2-i)(5-i)]/[(5+i)(5-i)]=
=(9 - 7i)/26
so
a= 9/26
b=-7/26
2007-01-09 03:16:57
·
answer #3
·
answered by Edward 7
·
0⤊
0⤋
Conjugate of 5+i = 5 - i
Mutiply numerator and denominator of (2-i)/(5+i) by 5-i
= (2-i)(5-i)/(5+i)(5-i)
= (10-7i-1)/25+1
= (9-7i)/26
=(9/26) - (7/26)i
2007-01-09 03:11:39
·
answer #4
·
answered by Som™ 6
·
2⤊
0⤋
(9/26) - (7/26)i
2007-01-09 03:11:38
·
answer #5
·
answered by bequalming 5
·
0⤊
1⤋
=[2+i]/[5+i]
=[2+i][5-i]/26
=[10+3i+1]/26
=11/26+[3/26]i
=.423+.115i
2007-01-09 03:51:50
·
answer #6
·
answered by openpsychy 6
·
0⤊
0⤋